PENGARUH RASIO KEUANGAN DAN FAKTOR LAINNYA TERHADAP FIRM VALUE DI INDONESIA - Theodora, Theresia; Sanjaya, Riki (E-Jurnal Akuntansi TSM, 2024)
This study aims to obtain empirical evidence and determine the effect of the independent variables Return on Asset, Debt to Asset Ratio, Current Ratio, Firm Size, Dividend Payout Ratio, Tax Avoidance, and Asset Growth on the dependent variable Firm Value. The research objects used in this study are consumer non-cyclicals and consumer cyclicals sectors companies listed on the Indonesia Stock Exchange (IDX) from the period 2020 to 2022. The sampling method in this study uses purposive sampling and implements the multiple regression method, there are 32 companies selected according to the criteria, with 96 data as the final sample. The results showed that Return on Asset and Debt to Asset Ratio have a positive influence on Firm Value. While Current Ratio, Firm Size, Dividend Payout Ratio, Tax Avoidance, and Asset Growth have no effect on Firm Value.